Computational fluid dynamics (CFD) analysis of a miniature wind turbine - Muhammad Izzuddin Hilmi, Zainal Abidin (2010)
This study is about the analysis of miniature wind turbine using Computational Fluids Dynamics (CFD). Wind energy is one of the renewable energy resources and the applications of wind turbine have been used in several countries. Basically there are three types of wind turbine that exists. Horizontal Axis Wind Turbine, Vertical Axis Wind Turbine and Offshore Wind Turbine. These three types of wind turbine have their own advantages and disadvantages. Horizontal Wind Turbines is the most popular type of wind turbine in practice nowadays. The miniature wind turbine is more practically used for residential area and has power output in the range of 400 W to 10 kW. Theoretically, in order to produce 10kW of power output, the wind speed must be at least 7 m/s. As for this study, the wind speed is at 4 m/s inaccordance to the Malaysian average wind speed. The maximum size of rotor blade for a miniature wind turbine is 7 m diameter. Analysis has been conducted using Computational Fluid Dynamics (CFD). In this project, the result is achieved by using COSMOFlow Work. In COSMOFlow Work, the value of Torque (Nm) measured is the value of force acting on the miniature rotor blade. A comparison study using Blade Element Momentum (BEM) theory has been conducted to ensure that the value of Torque from CFD and BEM in this project is synchronized. This is to prove that the analysis conducted correlated to the theory of wind turbine is correct and undoubful. As for the conclusion, this project has successfully achieved its targeted objectives.